2023
DOI: 10.1111/ssm.12573
|View full text |Cite
|
Sign up to set email alerts
|

The convergence of culture, technology and context: A pathway to reducing Mathophobia and improving achievement in mathematics

Abstract: This study explored the potency of CTCA in reducing math anxiety and promoting meaningful learning of mathematics among secondary school students. The study adopted a mixed‐method (explanatory sequential) design involving a quasi‐experimental design and individual in‐depth interviews. Participants were drawn from two schools, purposively selected within Lagos state educational district V. Three instruments: Set Theory Achievement Test, Math Anxiety Scale and Students' Perception about CTCA Interview Guide were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…These studies all took place at different times and locations, yet they all reported to have found no difference in the performance of male and female students sampled. A similar trend was reported by [4,47,64]. The results of these previous studies are comparable with the current study in that they all sampled secondary school students, focused on difficult concepts in STEM subjects, and used circular schools; however, unlike this study, which explored blended learning mode, they all limited their engagements with the students to face-to-face only.…”
Section: Effect Of Ctca On Students' Achievement (Retention) and Anxi...supporting
confidence: 89%
See 1 more Smart Citation
“…These studies all took place at different times and locations, yet they all reported to have found no difference in the performance of male and female students sampled. A similar trend was reported by [4,47,64]. The results of these previous studies are comparable with the current study in that they all sampled secondary school students, focused on difficult concepts in STEM subjects, and used circular schools; however, unlike this study, which explored blended learning mode, they all limited their engagements with the students to face-to-face only.…”
Section: Effect Of Ctca On Students' Achievement (Retention) and Anxi...supporting
confidence: 89%
“…The revised science anxiety scale developed by [64] was adopted for this study given its contextual relevance to the current study and population of interest. The instrument contained 20 words that depict states of the mind, ten of which are positive, and the other ten negative.…”
Section: Instrumentsmentioning
confidence: 99%